Intrazonal communities’ synanthropic flora of the Nothern Black Sea Region (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
It is presented a synanthropic flora’s review of 24 intrazonal vegetation classes, which numbers 273 species of vascular plants in the Nothern Black Sea Region. Systematical, biomorphologic, geographic, ecological analysis have been carried out. The flora and vegetation change forecast was done depending on an influence of economical factors, some questions of there’s optimization and next researches problems have been reviewed.
Keywords: Black See Region, flora, vegetation, invasive species.